A Mononuclear Lanthanide Metal Compounds Based on the Nitronyl Nitroxide Radicals: Synthesis, Crystal Structure, and Magnetic Properties. Issue 6 (2nd June 2016) - Qiao, Xue-Mei; Zhang, Chen-Xi; Kong, Yu-Kun; Zhang, Yu-Ying
Abstract : A complex [Er(hfac)3 [NITPh- p -Cl]2 ], (hfac=hexafluoroacetylacetonate; and NITPh- p -Cl=2-(4′-chlorophenyl)-4, 4, 5, 5-tetramethylimidazoline-1-oxyl-3-oxide) was synthesized and characterized structurally by X-ray crystal structure and magnetic measurements. X-ray crystal structure analysis revealed that the Er(III) ions are eight-coordinated and the complex has slightly distorted dodecahedron geometry. The variable temperature magnetic susceptibility measurements studies revealed that there are antiferromagnetic interactions between the Er(III) ions and the radicals in this complex.